2009
DOI: 10.1080/19331680903048832
|View full text |Cite
|
Sign up to set email alerts
|

Lost in Technology? Political Parties and the Online Campaigns of Constituency Candidates in Germany's Mixed Member Electoral System

Abstract: The Internet is changing the technological context of election campaigns in dramatic ways. The question of the larger impact of this development on the structures and strategies of election campaigns has stimulated two competing hypotheses. The orthodox view perceives the new medium as facilitating centralized election campaigns that allow party headquarters to target and mobilize groups of voters in more efficient and direct ways. A revisionist view stresses the Internet as a means for individual constituency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0
7

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(65 citation statements)
references
References 30 publications
2
56
0
7
Order By: Relevance
“…In their analysis of Facebook adoption by U.S. House of Representatives candidates, they have consistently found that the candidates with the greatest financial resources are the most likely to have employed Facebook. The positive effect of resources also extends to Twitter and beyond the United States with evidence from Australia (Gibson & McAllister, 2015), Austria (Dolezal, 2015), Germany (Zittel, 2009), andSwitzerland (Klinger, 2013) confirming the positive relationship. Thus, we might infer that with such overwhelming evidence we could classify this as an established pattern.…”
Section: Benefits and Costs Of Innovation: The Role Of Resourcesmentioning
confidence: 65%
“…In their analysis of Facebook adoption by U.S. House of Representatives candidates, they have consistently found that the candidates with the greatest financial resources are the most likely to have employed Facebook. The positive effect of resources also extends to Twitter and beyond the United States with evidence from Australia (Gibson & McAllister, 2015), Austria (Dolezal, 2015), Germany (Zittel, 2009), andSwitzerland (Klinger, 2013) confirming the positive relationship. Thus, we might infer that with such overwhelming evidence we could classify this as an established pattern.…”
Section: Benefits and Costs Of Innovation: The Role Of Resourcesmentioning
confidence: 65%
“…The parties control the nomination process, and once that process is over the possibility of being elected depends solely on the party vote. In systems that allow for more personal voting, such as the mixed German system or the Finnish system, new media might increase existing tendencies towards individualized campaigning (Zittel 2009). …”
Section: Discussionmentioning
confidence: 99%
“…The technology undoubtedly offers tools to better implement the central party campaign strategy, and enables parties to communicate more directly with the campaign organizations and voters. However, as mentioned above, new ICTs don't only present centrifugal incentives; they also provide individual candidates with new opportunities to run campaigns more independently of the central party and offer them a new platform for self-presentation (Zittel 2009). However, technology and technological use are shaped by existing practices (Neuman 1991(Neuman , 2001Anstead and Chadwick 2008;Karlsen 2010a), and to some extent the effect of technology on individualized campaigning will depend on the contextual characteristics of the campaign environment.…”
Section: Campaigns Candidates and Social Mediamentioning
confidence: 99%
See 2 more Smart Citations